Decision making in organisations hostile to knowledge sharing - Snejina Michailova; Kenneth Husted (Journal for East European Management Studies, 2004)
This paper focuses on some of the specificities of decision making in Russian organisations. These companies usually have a highly centralized decisionmaking. Paradoxically, Russian firms are also known for their relatively high level of hostility towards knowledge sharing. Both characteristics constitute a dangerous combination for strategic decision-making processes in the organisations and their ability to commit resources to adequate actions. On the basis of 53 interviews in 25 companies over the last six years, this paper analyses the interface between different dimensions of knowledge sharing hostility and the consequences these have for strategic decision making. – – Der Aufsatz befasst sich mit einigen Merkmalen der Entscheidungsfindung in russischen Organisationen. Diesbezügliche Strukturen in Unternehmen sind normalerweise sehr stark. Paradoxerweise sind russische Firmen auch für ihre Einstellung gegen Informationsaustausch bekannt. Beide Merkmale stellen eine gefährliche Kombination für strategische Entscheidungsfindungsprozesse und für die Allokation von Ressourcen dar. Auf der Basis von 53 Interviews in 25 Firmen in den letzten 6 Jahren analysiert der Aufsatz das Interface zwischen verschiedenen Dimensionen der Einstellung gegen Informationsaustausch und den darausfolgenden Konsequenzen für die strategische Entscheidungsfindung.
Keywords: 650; Russian organisations; knowledge sharing hostility; strategic decision making